2015
DOI: 10.1007/978-3-319-20892-3_37
|View full text |Cite
|
Sign up to set email alerts
|

Age(ism) in Digital Information Provision: The Case of Online Public Services for Older Adults

Abstract: Abstract. This paper draws on an empirical investigation of how older people are represented on the websites providing social care service information in the inner London Boroughs. My research questions follow the work of Loos [1] [2] on the relationship between representations of older age, information accessibility and access to digital services. Mirroring Loos and reflecting the specificities of the fieldwork my investigation found older people were largely invisible as a diverse group of citizens in the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Some studies have described this generation gap as merely a temporary phenomenon because today's youth are growing up with nearly universal access to digital technology. For example, in 2013, 50% of people over age 65 in the UK used the Internet (Sourbati, 2015). However, the majority of adults in their 80s have never used the Internet at work.…”
Section: Challenges Of Digitalization In Care and Social Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have described this generation gap as merely a temporary phenomenon because today's youth are growing up with nearly universal access to digital technology. For example, in 2013, 50% of people over age 65 in the UK used the Internet (Sourbati, 2015). However, the majority of adults in their 80s have never used the Internet at work.…”
Section: Challenges Of Digitalization In Care and Social Servicesmentioning
confidence: 99%
“…Note that doubts about older adults' abilities to learn or to adapt to changes often manifest an ageist stereotype rather than objective facts. As pointed out by Sourbati (2015), older adults are treated as a "residual category" when new media technologies are analyzed. Generally, the only older adults to be depicted on social services Web pages are frail, making it difficult for other, more vibrant older adults to identify with the images they see on these sites.…”
Section: Challenges Of Digitalization In Care and Social Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Students can provide assistance and instructions to seniors in the field of modern technologies, including the use of tablet computers and internet banking (Fig. 23.2), exploring the digital world which can pose problems in terms of accessibility and be ageist in its own way (Sourbati 2015). Both projects showed that the people involved (students, seniors and lecturers) gained insights from the interaction with each other, and that further research was needed as to how seniors could be involved in the educational programme in the most fitting and beneficial way.…”
Section: Managementmentioning
confidence: 99%
“…According to Lee et al (2011), the ability to access a computer does not depend principally on age; rather, it is linked to education level, income, and living situation (solitary or shared). Differences between the sexes correlate with education and income, as well as other variables such as ethnicity, and show the diversity in using new technologies Sourbati, 2015). The concept of "age heterogeneity" implies inequalities within the older population, determined by restriction in social space, communication facilities, health, and leisure, among others (Sourbati, 2015).…”
Section: Challenges Of Digitalization In Care and Social Servicesmentioning
confidence: 99%